Бани византийского Херсона (VI-X вв.) - Сорочан, С. Б. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryS. Sorochan. The Baths of the Byzantian Cherson (VI–X Centuries)The research written and especially archeological sources of a history Cherson during an early middle ages gives a conclusion about existence in city several baths. One bathhouse was at centre of «citadel». It had gone through two large repairs and acted at second half VI–middle IX centuries. Other bath existed in VII–X centuries on northern coast near the large bazylik ¹ 22. Third bath was at centre housing estates III, in east part of city. It was constructed in VI–VII centuries and with alterations, repairs acted to XI–XII centuries. Probably, one bath-house entered into a complex of bazylik ¹ 23. The bath in block VII is known only under the drawings executed before construction of cathedral S. Vladymir on a place large agora. All of them had some rooms and gypokaust system, that specifies on continuity with graeco-roman construction. The affinity to temples allows notice the control for baths on the part of church authorities, but it not the basis for the conclusions about decline and disappearrance the baths in «dark ages».